The Impact of Unemployment on Economic Growth in Pakistan: An Empirical Investigation - Shah, Salyha Zulfiqar Ali; Shabbir, Mah Rukh; Parveen, Sabiha (iRASD Journal of Economics, 2022)
This study has attempted to scrutinize the impact of unemployment on the growth rate during the period 1974 to 2020 in Pakistan. This study has employed the Autoregressive Distributed Lag (ARDL) technique for empirical investigation. GDP growth rate is a dependent variable, employed as a proxy for economic growth. In the present study, explanatory variables are unemployment, population growth rate, rate of inflation, foreign direct investment and government expenditure. The empirical findings from the study show that unemployment and inflation rates both show a negative relationship with economic growth and are significant statistically. The population growth rate has a positive and statistically significant impact on economic growth. Short-run cointegration exists between the variables. It is suggested from the results that government should adopt adequate measures to generate employment opportunities to accelerate economic growth and reduce unemployment in the country.